Unilocular radiolucency of mandibular angle region –A clinicopathological Conference - Anil Mangutti; Dishan Shah; Jigar Patel; Jignesh Maheshwari (Journal of Head & Neck Physicians and Surgeons, 2015)
Calcifying Cystic Odontogenic Tumor (CCOT) constitutes 1% of all jaw cysts and considered as one of the rarest odontogenic lesions. It's a group of odontogenic entities which exhibits variety of clinical and biological behaviors. Even after many classifications and sub classifications COC remains a tough nut to crack for clinicians and pathologists. According to recent WHO classification of 2005 it has been reclassified as a tumor due to its diverse nature. Ameloblastomatous Proliferating type is very rare variant of CCOT which is not widely described in literature. This Clinicopathological conference presents one such case in young female patient and also discuss in detail about the differential diagnosis and management of such cases.